Terahertz wave interaction with metallic nanostructures - Kang, Ji-Hun; Kim, Dai-Sik; Seo, Minah (WALTER DE GRUYTER GMBH, 2018)
Understanding light interaction with metallic structures provides opportunities of manipulation of light, and is at the core of various research areas including terahertz (THz) optics from which diverse applications are now emerging. For instance, THz waves take full advantage of the interaction to have strong field enhancement that compensates their relatively low photon energy. As the THz field enhancement have boosted THz nonlinear studies and relevant applications, further understanding of light interaction with metallic structures is essential for advanced manipulation of light that will bring about subsequent development of THz optics. In this review, we discuss THz wave interaction with deep sub-wavelength nano structures. With focusing on the THz field enhancement by nano structures, we review fundamentals of giant field enhancement that emerges from non-resonant and resonant interactions of THz waves with nano structures in both sub- and super- skin-depth thicknesses. From that, we introduce surprisingly simple description of the field enhancement valid over many orders of magnitudes of conductivity of metal as well as many orders of magnitudes of the metal thickness. We also discuss THz interaction with structures in angstrom scale, by reviewing plasmonic quantum effect and electron tunneling with consequent nonlinear behaviors. Finally, as applications of THz interaction with nano structures, we introduce new types of THz molecule sensors, exhibiting ultrasensitive and highly selective functionalities.
Keywords: TIME-DOMAIN SPECTROSCOPY; NEAR-FIELD ENHANCEMENT; ELECTRON-BEAM LITHOGRAPHY; METAMATERIAL ABSORBER; SUBWAVELENGTH HOLE; OPTICAL-PROPERTIES; EXTRAORDINARY TRANSMISSION; SLIT ARRAYS; GRAPHENE PLASMONICS; LIGHT TRANSMISSION